Tool geometry evaluation for carbon reinforced composite laminates - Daniel Joaquim Silva Gonçalves (2009)
The subject of this work is the study of drilling conditions and tool geometry in order to minimize delamination damage. Delamination is evaluated by enhanced radiography and damage criteria applied to compare different tools and cutting parameters.